(untitled) (E Global Congress, 2025)
The rapid expansion of e-commerce has transformed traditional business models, requiring advanced accounting methods to ensure financial transparency, tax compliance, and accurate reporting. This article explores the unique accounting challenges faced by e-commerce companies, including revenue recognition, digital taxation, inventory valuation, and fraud detection. Additionally, it examines innovations in accounting technology, such as automation, artificial intelligence, and blockchain, which enhance accuracy and efficiency in financial reporting. By addressing these challenges and adopting modern solutions, e-commerce businesses can improve financial management and regulatory compliance, ultimately contributing to their long-term success.